Hsa_circ_0001944 regulates apoptosis by regulating the binding of PARP1 and HuR in leukemia and malignant transformed cells induced by hydroquinone. Issue 2 (30th November 2022) - Zhong, Bohuan; Ling, Xiaoxuan; Meng, Jinxue; Han, Yali; Zhang, Haiqiao; Liu, Zhidong; Chen, Jialong; Zhang, He; Pan, Zhijie; Liu, Linhua
Abstract: Hydroquinone (HQ) is one of the major metabolites of benzene and can cause abnormal gene expression. It is a known carcinogen that alters cell cycle disruption and cell proliferation. However, its chemical mechanism remain a mystery. Circular RNAs (circRNAs) are a subtype of noncoding RNAs (ncRNAs) that play a variety of roles in biological processes. Hsa_circ_001944 expression was upregulated in 30 leukemia patients and HQ‐induced malignant transformed TK6 cells. Hsa_circ_001944 silencing inhibited the growth of HQ‐TK6 cells and halted the cell cycle. The silencing of hsa_circ_0001944 led to increased cell accumulation in G1 versus S phase, increased apoptosis in the sh1944 versus the shNC group, and increased levels of DNA damage (γ‐H2AX), leading to cell cycle arrest. In summary, inhibition of hsa_circ_001944 restricted cell growth by inhibiting cell cycle arrest and induced growth of HQ‐TK6 cells by modulating PARP1 expression. Hsa_circ_0001944 targeted HuR, which is a kind of RNA‐binding protein, to control PARP1 expression via RNAinter, RBPmap, and RBPdb. Fluorescence in situ hybridization combined with immunofluorescent labeling and western blotting experiments showed that hsa_circ_001944 was able to dissociate HuR and PARP1 binding in HQ‐TK6 cells, control PARP1 production, and ultimately alter the PARP1/H‐Ras pathway.